Dream Tree Innovation FOR Training Leadership of Pancasila Student Profile At State Elementary School 1 Telaga (Global Scientific Review, 2022)
This research aims to instill leadership qualities from an early age. This research is deliberately done so that it is hoped that it will form a leadership spirit from an early age. This study uses the observation method. The results of this study indicate that there is a leadership spirit among these students to become a leader. The ability to become a leader is demonstrated very well by the students at State Elementary School 1 Telaga